Soil fertility and nutrition in cacao cultivation (Theobroma cacao L.) in three soils of Tabasco, Mexico - Francisco-Santiago, Sandra Patricia; Palma-López, David Jesús; Sánchez-Hernández, Rufo; Obrador-Olán, José Jesús; García-Alamilla, Pedro (REVISTA TERRA LATINOAMERICANA, 2023)
Cocoa is a traditional crop in southern Mexico, although its productivity is low due to edaphic and nutritional limitations. Hence, the aim of our research was to diagnose edaphic fertility and the nutritional content of cacao plantations in the main groups of cultivated soils in La Chontalpa, the main cocoa production area of Tabasco state, to identify the edaphic and nutritional variables that restrict crop productivity. Through the analysis of satellite images, sampling sites were selected in representative soils of the study area and the coordinates were geopositioned to locate them. Soil profiles were described to classify the soils of the sampling sites. Soil samples were collected at depths of 0-10, 10-30 and 30-50 cm, to determine variables of soil fertility. In producer trees, foliar samples were collected to determine the concentrations of macronutrients. The results indicate that the plantations are cultivated on Vertisols, Cambisols and Fluvisols, which do not show restrictions in most of the edaphic properties. However, due to the low C/N ratio (< 12) of the soils, there is a decrease in the OM and N contents, which are added to a K deficit, causing low concentrations of both macronutrients in the foliage of the plants. In conclusion, the main edaphic restrictions that can af fect cocoa cultivation in La Chontalpa are the rapid loss of OM and a deficit of N and K in the soil, which cause low concentrations of both nutrients in the foliage of the trees.